INCIDENCE AND MOLECULAR DETECTION OF OCHRATOXIGENIC FUNGI FROM INDIAN CEREAL GRAINS - K. VENKATA REDDY; NAVEEN. K; I. BHASKAR REDDY (International Journal of Pharma and Bio Sciences, 2013)
A total of 150 cereal samples from three regions of Southern India i.e. Karnataka, Andhra Pradesh and Tamilnadu were collected during winter 2010 – 2012 to determine the ochratoxigenic fungal incidences. A total of 150 fungal isolates comprising, Aspergillus ochraceus, A. niger and Penicillium verrucosum were recovered and tested for ochratoxin A (OTA) production. Chemotype determination of fungal isolates was carried out by molecular and chemical analysis through PCR and HPLC methods. Out of 3 study sites the incidence of ochratoxigenic Aspergillus and Penicillium species were recorded as 30%, 33% and 22 % in Karnataka, Andhra Pradesh and Tamilnadu regions respectively. Based on PCR results A. ochraceus (36), A. niger (29) and P. verrucosum (38) were recorded as OTA chemotypes. The mean concentrations of OTA were determined as 12.2 μg/kg, 15.6 μg/kg and 8.3 μg/kg for wheat, maize and rice, samples respectively. The results of the present study suggest that the PCR developed can be used to determine ochratoxigenic fungal contamination in agricultural commodities such as cereals and other food grains. Moreover, the high levels of OTA contamination recorded in present study warrants that there is a need to undertake mycotoxin awareness creation programme among the different cereal growing regions of India to reduce risk of its harmful effects to human and other farm animals.